2022
DOI: 10.1002/hep.32285
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fibrosis 2022: Unmet needs and a blueprint for the future

Abstract: Steady progress over four decades toward understanding the pathogenesis and clinical consequences of hepatic fibrosis has led to the expectation of effective antifibrotic drugs, yet none has been approved. Thus, an assessment of the field is timely, to clarify priorities and accelerate progress. Here, we highlight the successes to date but, more importantly, identify gaps and unmet needs, both experimentally and clinically. These include the need to better define cell-cell interactions and etiology-specific el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
206
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(212 citation statements)
references
References 154 publications
1
206
0
5
Order By: Relevance
“…Instances of non-alcoholic steatohepatitis (NASH)-induced liver fibrosis and cirrhosis have recently increased, and several relevant clinical trials have been conducted mainly in Europe and the United States, although many have been discontinued in the middle of development. 7 , 8 , 9 One reason is the use of pathological diagnosis using liver biopsy as a method to confirm the anti-fibrotic therapeutic effect. 7 Although long-standing problems associated with sampling error have been noted, it is suggested that long time periods are required to observe the effect of fibre reduction due to the strength of the connections between fibres that have progressed to cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instances of non-alcoholic steatohepatitis (NASH)-induced liver fibrosis and cirrhosis have recently increased, and several relevant clinical trials have been conducted mainly in Europe and the United States, although many have been discontinued in the middle of development. 7 , 8 , 9 One reason is the use of pathological diagnosis using liver biopsy as a method to confirm the anti-fibrotic therapeutic effect. 7 Although long-standing problems associated with sampling error have been noted, it is suggested that long time periods are required to observe the effect of fibre reduction due to the strength of the connections between fibres that have progressed to cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 One reason is the use of pathological diagnosis using liver biopsy as a method to confirm the anti-fibrotic therapeutic effect. 7 Although long-standing problems associated with sampling error have been noted, it is suggested that long time periods are required to observe the effect of fibre reduction due to the strength of the connections between fibres that have progressed to cirrhosis. Recently, there have been more studies on pre-stage fibrosis (F2-3) than on liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although accumulation of collagen ECM is the de facto definition of fibrosis, the changes to the hepatic ECM that happen during both processes are much diverse than those that happen to collagen (9). Likewise, although it is understood that hepatic fibrosis resolution involves more than simple clearance of collagen ECM, the process and its mediators are incompletely understood, at best (38).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the Introduction, collagenous ECM accumulation has been the major focus in the field of hepatic fibrosis (2). Likewise, proteases involved in resolution of collagenous ECM (e.g., MMP2 and MMP9) have also received a sizeable amount of attention (38). Once the technical limitations to identifying peptide fragments of degraded proteins informatically was overcome (42, 43), the fragment sequence and putative cleavage site may yield new information on proteases involved.…”
Section: Discussionmentioning
confidence: 99%
“…Because sustained fibrosis leads to the development of end-stage cirrhosis and generates a microenvironment favorable to the development of primary liver cancer [ 1 ], early-stage treatment of liver fibrosis is essential. To date, although some antifibrotic agents have reached clinical trials, effective therapy for fibrosis and cirrhosis in clinical practice remains an unmet medical need [ 2 ].…”
Section: Introductionmentioning
confidence: 99%